Pijat Oksitosin terhadap Pengeluaran ASI pada Ibu Postpartum Multipara - Beksi Yaturahmi; Nia Desriva; Yesi Septina Wati; Meirita Herawati (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of oxytocin massage on breast milk production in multiparous postpartum mothers in the Kota Baru Community Health Center (UPT Puskesmas), Indragiri Hulu Regency. The method used was a quantitative study with a quasi-experimental design, employing a one-group pretest-posttest design. The results showed an increase in breast milk production after oxytocin massage, as indicated by significant differences between pretest and posttest scores for infant urination frequency (p = 0.003) and infant bowel movement frequency (p = 0.002). In conclusion, oxytocin massage affects breast milk production in multiparous postpartum mothers at the Kota Baru Community Health Center in Indragiri Hulu Regency in 2025.   Keywords: Multiparous Postpartum Mothers, Oxytocin Massage, Breast Milk Production